Hubungan Antara Stress Dengan Kejadian Kekambuhan Gastritis Pada Remaja Di Pondok Pesantren X Kudus - Arifiansyah, Khilyah Tasya Putri; Haiya, Nutrisi Nu'im; Ardian, Iwan (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah., 2022)
Abstract Background: Gastritis is inflammation caused by infection or irritation of the gastric mucosa dueto irregular eating patterns, consumption of coffee, alcohol, consumption of long-term painrelievers, psychological stress, physical stress, and infection by the Helicobacter pylori bacteria.Gastritis which causes stomach pain, such as bloating, nausea, and having a headache that causesuninterrupted daily activities, stomach cancer, and even death. Stress has a negative impact on theneuroendocrine digestive system, so you can be at risk of developing gastritis due to stressfulconditions, and stomach acid will increase.Methods: the study was a cross sectional quantitative study. Data collection using a questionnairewith 120 respondents consisting of 60 cases 60 controls with purposive sampling technique. Dataprocessing used the chi-square test.Results: The study was conducted on respondents who were homogeneous who were female andhad the characteristics of the case group aged 16 years as much as 35 (30%), high schooleducation as much as 32 (53.3%), and stress as much as 30 (50%). The results of the study in thecase group showed that stress was 30 (90.9%) and no stress was 30 (9.1%).Conclusion: There is a relationship between stress and the incidence of gastritis recurrence inadolescents at Pondok Pesantren X Kudus, with the chi-square test the result is p value = 0,000.Key words: Adolescence, Stress and Gastritis Recurrence Incidence